Profil Senyawa Volatil Identitas Nutmeg Oil, Patchouli Oil dan Fresh Ginger Oil Asal Indonesia - Riyadi, Erwin; Andarwulan, Nuri; Faridah, Didah Nur (Jurnal Mutu Pangan : Indonesian Journal of Food Quality, 2014)
The aim of this study was to identify the volatile compounds of nutmeg oil, patchouli and fresh ginger oil from Indonesia and to conduct gap analysis of its volatile compounds profile with both national and international standards. Nutmeg oils were collected from Sulawesi and Java. Patchouli oils were collected from Sulawesi, Java and Sumatra. Fresh ginger oil was collected from Java. The volatile oils were analyzed by Gas Chromatography (GC) and Gas Chromatography Mass Spectrometry (GC-MS) for identification and quantification of their volatile compounds. 35 compounds were identified in Sulawesi and Java nutmeg oil, and the major compounds were alpha pinene, sabinene, beta pinene and myristicin. The profile of volatile compounds of these nutmeg oils were in specification of Firmenich standard and out of specification of European Parmaque (EP) standard. The quality of Java nutmeg oil was found better than that of Sulawesi nutmeg oil. In Sulawesi, Java and Sumatra patchouli oils, 33 compounds were identified. Patchouli alcohol was the major compound in patchouli oil. The second major compounds were alpha guaiene, seychellene, alpha patchouelene and alpha bulnesene. Patchouli oil from Sulawesi was in specification of International Standard (ISO and Firmenich standard) and out of speci cation of national standard. (SNI) However, the patchouli oil from Java and Sumatra were in specification of all standards. Fresh ginger oil contained 70 compounds with champene, beta phellandrene, alpha curcumene, zingiberene and beta sesquephelandrene as major compounds.